2020
DOI: 10.1101/2020.10.30.361907
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Macrophages orchestrate the expansion of a pro-angiogenic perivascular niche during cancer progression

Abstract: Tumor associated macrophages (TAMs) are a highly plastic stromal cell type which are exquisitely polarized by the tumor microenvironment to support cancer progression. Single-cell RNA-sequencing (scRNA-seq) of TAMs from a spontaneous murine model of mammary adenocarcinoma (MMTV-PyMT) identified three distinct polarization trajectories for these cells within the tumor microenvironment. We reveal sub-divisions within the protumoral TAM population with one subset expressing Lyve-1 and residing in a spatial niche … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…Once these factors bind to their respective receptor, monocytes undergo polarization and maturation into more specialised TAM phenotypes through downstream signal transduction pathways altering transcription within these cells ( 68 ). Recently, it has been identified that TAM polarization can be refined to a three-way polarization program in a spontaneous murine model of breast cancer ( 11 ). This three-way program is broadly split into an alternatively-activated-like, angiogenic/immunosuppressive, and inflammatory phenotypic specialization of these cells ( 11 ).…”
Section: Phase 2: Macrophage Polarizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Once these factors bind to their respective receptor, monocytes undergo polarization and maturation into more specialised TAM phenotypes through downstream signal transduction pathways altering transcription within these cells ( 68 ). Recently, it has been identified that TAM polarization can be refined to a three-way polarization program in a spontaneous murine model of breast cancer ( 11 ). This three-way program is broadly split into an alternatively-activated-like, angiogenic/immunosuppressive, and inflammatory phenotypic specialization of these cells ( 11 ).…”
Section: Phase 2: Macrophage Polarizationmentioning
confidence: 99%
“…Recently, it has been identified that TAM polarization can be refined to a three-way polarization program in a spontaneous murine model of breast cancer ( 11 ). This three-way program is broadly split into an alternatively-activated-like, angiogenic/immunosuppressive, and inflammatory phenotypic specialization of these cells ( 11 ).…”
Section: Phase 2: Macrophage Polarizationmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, LYVE‐1 knockdown in tumor cells not only inhibited their lymphogenic activity but also impaired tumor cell metastasis in vivo 10 . A recent preprint study reported that selective targeting of LYVE‐1 +ve tumor‐associated macrophages significantly impairs the growth of cancer‐related vasculature and hence slows tumor development 11 . Furthermore, targeting LYVE‐1 revealed therapeutic and prognostic potential in common aggressive neoplasms including breast cancer, wherein lymph node metastasis (LNM) can influence the treatment modality and survival expectancy 12,13 …”
Section: Introductionmentioning
confidence: 99%
“…10 A recent preprint study reported that selective targeting of LYVE-1 +ve tumor-associated macrophages significantly impairs the growth of cancer-related vasculature and hence slows tumor development. 11 Furthermore, targeting LYVE-1 revealed therapeutic and prognostic potential in common aggressive neoplasms including breast cancer, wherein lymph node metastasis (LNM) can influence the treatment modality and survival expectancy. 12,13 Numerous studies have investigated the association between LYVE-1 status and the clinical outcome of cancer; however, results are variable.…”
Section: Introductionmentioning
confidence: 99%